2021
DOI: 10.1108/mip-09-2020-0421
|View full text |Cite
|
Sign up to set email alerts
|

Gen Y consumers' brand loyalty: a brand romance perspective

Abstract: PurposeAs Generation Y is considered to be a lucrative segment for emerging devices, this study investigates the effect of emotional brand attachment, from the brand romance perspective, on brand loyalty of Generation Y smartphone users. Furthermore, this study examines gender differences in the same relationship.Design/methodology/approachThe study adopted a cross-sectional survey method and data was collected from 300 respondents. Data was analyzed using the structural equation modelling (SEM) approach and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Many researchers have recently focused on investigating consumer brand loyalty from various perspectives (Boateng et al, 2020;Rathnayake, 2021;Atulkar, 2020). Consumer loyalty is described as a consumer's behavioral intentions and assessments of the likelihood of buying a brand (Busser and Shulga, 2019).…”
Section: Consumer Loyaltymentioning
confidence: 99%
“…Many researchers have recently focused on investigating consumer brand loyalty from various perspectives (Boateng et al, 2020;Rathnayake, 2021;Atulkar, 2020). Consumer loyalty is described as a consumer's behavioral intentions and assessments of the likelihood of buying a brand (Busser and Shulga, 2019).…”
Section: Consumer Loyaltymentioning
confidence: 99%
“…In addition, Lam and Shankar (2014) stated that prior researchers have largely investigated the drivers of brand loyalty in general but not the smartphone market in particular. In the smartphone market, Rathnayake (2021) stressed the need of identifying the predictors of consumer loyalty. As a result, an integrated brand loyalty study in a smartphone scenario is deemed necessary and worthwhile (Islam et al, 2019; Rasool et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Hsieh et al, 2021, Petzer et al, 2014, Rathnayake, 2021 found that the dimensions of brand romance had a significant impact on brand loyalty. When customers see a brand like a romantic partner, the relationships between the brand and the customers become less costly to retain (Hess, Story, & Danes, 2011).…”
Section: Introductionmentioning
confidence: 91%